Fabrication and physiochemical properties of chitosan/beeswax biofilm for wound healing applications - Mohd Roslan, Wan Muhammad Faiz (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Chitosan-based dressings with antimicrobial properties aid wound healing when applied to wounds. Beeswax shows therapeutic potential in wound healing. Combining chitosan and beeswax enhances wound healing capacity. A solution casting method was used to create the chitosan and beeswax biofilm, allowing for varying amounts of beeswax from 1g to 5g. Glutaraldehyde cross-linking formed a firm biofilm. Characterization involved SEM, FTIR, contact angle, and AFM. Beeswax addition resulted in a rough and jagged surface. FTIR confirmed bonding between chitosan and beeswax. Modifications targeted chitosan's hydrophilic properties, increasing biofilm hydrophobicity. AFM demonstrated increased surface roughness with beeswax addition. Overall, the biofilm fabrication was successful for wound healing applications.